1990
DOI: 10.1097/00000658-199003000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Respiratory Symptoms and Occult Gastroesophageal Reflux

Abstract: Seventy-seven patients with a primary complaint of persistent cough, wheezing, and/or recurrent pneumonia were evaluated for the presence of occult gastroesophageal reflux disease. Fifty-four patients (70%) had increased esophageal acid exposure on 24-hour pH monitoring of the distal esophagus. In 28% of these patients the respiratory symptoms were thought to be due to aspiration because they occurred during or within 3 minutes after a reflux episode. In the other patients, the respiratory symptoms were either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(17 citation statements)
references
References 9 publications
0
14
0
3
Order By: Relevance
“…Gustafsson et al reported pathological reflux in 50% of asthmatic children in the proximal esophagus and in 16% in the proximal esophagus [29]. DeMeester et al reported that 50% of patients with chronic respiratory symptoms with proximal reflux had esophageal dysmotility [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Gustafsson et al reported pathological reflux in 50% of asthmatic children in the proximal esophagus and in 16% in the proximal esophagus [29]. DeMeester et al reported that 50% of patients with chronic respiratory symptoms with proximal reflux had esophageal dysmotility [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The severity o f these symtoms was graded into 4 categories, absent, mild, moderate or severe, according to the crite ria of De Mecster et al [8].…”
Section: Clinical Analysismentioning
confidence: 99%
“…However, recent reviews analysing the data in the literature on the outcome of patients with asthma undergoing anti-reflux surgery highlighted that this surgical approach, improving symptoms and decreasing the need for medications, has a great impact on the patients quality of life. These studies showed an improvement of reflux symptoms, asthma symptoms and pulmonary function in 90 %, 79%, and 27% of operated patients respectively, and a postoperative reduction of medication in 88% (7,22). Many other papers evaluated the incidence of reflux and supraoesophageal symptoms and many doubts are still evident about the need of surgery in this paediatric population (1, 4, 8,11 ± 18, 21, 25, 26).…”
Section: Introductionmentioning
confidence: 98%